New criteria for certain classes containing generalised differential operator - Adnan Alamoush; Maslina Darus (Penerbit Universiti Kebangsaan Malaysia, 2013)
The main objective of this study is to generalise a differential operator. This generalised differential operator reduces to many known operators studied by various authors. New subclasses containing generalisation of differential operator are introduced. Characterisation and other properties of these subclasses are given.